2015
DOI: 10.2169/internalmedicine.54.4144
|View full text |Cite
|
Sign up to set email alerts
|

A Reduction of HbA1c after 3 Months Predicts 2-year Responsiveness to Sitagliptin Treatment

Abstract: Objective This retrospective study evaluated the long-term efficacy of sitagliptin and the factors contributing to its glucose-lowering effect. Methods Six hundred and sixteen dipeptidyl peptidase-4 inhibitor-naïve outpatients with type 2 diabetes who began sitagliptin treatment between December 1, 2009 and December 31, 2011 were included in this study. The inclusion criteria were that the patient had regularly visited our hospital for a period of ! 700 days from the initiation of sitagliptin treatment and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Although, if study drug doesn’t work enough, to fix medication for a long time is not good for patients. On the other hand, Nishimura et al reported that a patient’s HbA1c change at 3 months may be a predictor of their HbA1c change at 24 months [11]. And our study also showed the HbA1c level of 12 month was similar to 3 month.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although, if study drug doesn’t work enough, to fix medication for a long time is not good for patients. On the other hand, Nishimura et al reported that a patient’s HbA1c change at 3 months may be a predictor of their HbA1c change at 24 months [11]. And our study also showed the HbA1c level of 12 month was similar to 3 month.…”
Section: Discussionsupporting
confidence: 73%
“…In many studies, sitagliptin reportedly improved HbA1c and fasting blood glucose levels both as a single-drug therapy [3, 810] and as a combination therapy with other antidiabetic drugs [4, 5, 11]. In our study, we excluded patients undergoing insulin use, also some clinical trials [12, 13] reported about the combination therapy about sitagliptin and insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is diagnosed based on symptoms, fasting plasma glucose concentration, oral glucose tolerance test, and glycated Hb (HbA1c) measurement. Among these, HbA1c reflects blood glucose status over the three prior months and is widely used because it plays an important role in predicting the prognosis of the therapeutic effect as well as in diagnosis and follow-up [34]. As HbA1c test results have become more important and the demand for the test has increased, fast and accurate reporting of HbA1c test results has become one of the main challenges.…”
Section: Introductionmentioning
confidence: 99%